Electrical characterization of p-Si/fullerene-C60 heterojunction photodiode - Yakuphanoğlu, Fahrettin; Farooq, W. A. (Natl Inst Optoelectronics, 2011)
Photovoltaic and electronic properties of p-Si/C-60 device have been investigated by current-voltage and capacitance-voltage methods. The ideality factor n and barrier height (I)B values of the p-n junction were found to be 2.92 and 0.83 eV respectively. Current-voltage characteristic of the device indicates a non-ideal behavior due to ideality factor higher than unity. Capacitance-voltage characteristic of the device indicate an abrupt junction behavior. Electrical characterization results confirms that p-Si/C60 device is an photodiode with the calculated electronic parameters, maximum open circuit voltage V-oc of 150 mV and short-circuit current I-sc of 12.1 nA
Keywords: Photodiode; Organic semiconductor; Fullerene-C-60